Mercadeo informal estrategia de pequeña empresa: la necesidad obliga - Gastañaduy, Alfonso (1992)
It presents the case of a textile entrepreneur facing a difficult situation due to the oversizing of his business and the neglect of marketing variables, at a time when inflation levels are high and a sharp recession process is beginning. Forced by necessity, he has to close two of his four stores, liquidate his garment factory and return to informality. After taking a marketing management course at a prestigious institution, he sets about the task of preparing his strategic planning. The case is a good opportunity for students to deepen their understanding of the strategic planning process: the mission; the situational analysis, risks and opportunities of the general environment of the country and the competitive environment (strengths and weaknesses); and finally the objectives and strategies, all within a framework of free importation in a market economy context.